NKTR-255, a novel polymer-conjugated rhIL-15 with potent antitumor efficacy. Issue 5 (17th May 2021) - Miyazaki, Takahiro; Maiti, Mekhala; Hennessy, Marlene; Chang, Thomas; Kuo, Peiwen; Addepalli, Murali; Obalapur, Palakshi; Sheibani, Sara; Wilczek, Joanna; Pena, Rhoneil; Quach, Phi; Cetz, Janet; et al.
Abstract : Background: NKTR-255 is a novel polyethylene glycol-conjugate of recombinant human interleukin-15 (rhIL-15), which was designed to retain all known receptor binding interactions of the IL-15 molecule. We explored the biologic and pharmacologic differences between endogenous IL-15 receptor α (IL-15Rα)-dependent (NKTR-255 and rhIL-15) and IL-15Rα-independent (precomplexed rhIL-15/IL-15Rα) cytokines. Methods: In vitro pharmacological properties of rhIL-15, NKTR-255 and precomplex cytokines (rhIL-15/IL-15Rα and rhIL-15 N72D/IL-15Rα Fc) were investigated in receptor binding, signaling and cell function. In vivo pharmacokinetic (PK) and pharmacodynamic profile of the cytokines were evaluated in normal mice. Finally, immunomodulatory effect and antitumor activity were assessed in a Daudi lymphoma model. Results: NKTR-255 and rhIL-15 exhibited similar in vitro properties in receptor affinity, signaling and leukocyte degranulation, which collectively differed from precomplexed cytokines. Notably, NKTR-255 and rhIL-15 stimulated greater granzyme B secretion in human peripheral blood mononuclear cells versus precomplexed cytokines. In vivo, NKTR-255 exhibited a PK profile with reduced clearance and a longer half-life relative to rhIL-15 and demonstrated prolonged IL-15R engagement in lymphocytes compared with only transient engagement observed for rhIL-15 and precomplexed rhIL-15 N72D/IL-15Rα Fc. As a consequent, NKTR-255 provided a durable and sustained proliferation and activation of natural killer (NK) and CD8 + T cells. Importantly, NKTR-255 is more effective than the precomplexed cytokine at inducing functionally competent, cytotoxic NK cells in the tumor microenvironment and the properties of NKTR-255 translated into superior antitumor activity in a B-cell lymphoma model versus the precomplexed cytokine. Conclusions: Our results show that the novel immunotherapeutic, NKTR-255, retains the full spectrum of IL-15 biology, but with improved PK properties, over rhIL-15. These findings support the ongoing phase 1 first-in-human trial (NCT04136756 ) of NKTR-255 in participants with relapsed or refractory hematologic malignancies, potentially advancing rhIL-15-based immunotherapies for the treatment of cancer.